Uso do preservativo por pessoas vivendo com HIV e parceiros soroconcordantes e sorodiscordantes - Siqueira, Larissa Rodrigues (2023)
The objective was to verify the factors associated with condom use in People Living with HIV (PLHIV) and seroconcordant and serodiscordant partners, and its relationship with quality of life (QoL) and self-efficacy in condom use. Cross-sectional and comparative study, carried out in three outpatient clinics in Fortaleza-CE: Universitary Hospital Walter Cantídio, Hospital São José and Policlínica José de Alencar. The sample consisted of 190 patients (95 seroconcordant and 95 serodiscordant). Inclusion criteria: PLHIV of both sexes, over 18 years old, sexually active, with a steady or casual partner, who have used a condom. Exclusion criteria: pregnancy and conditions that interfered with the study. Data collected from March 2021 to September 2022, through interviews and application of instruments: Sociodemographic, Clinical, Epidemiological and Vulnerability Form for PLHIV, Condom Use Self-Efficacy Scale and Instrument for Assessing the QoL of PLHIV. Descriptive statistics and Shapiro-Wilk normality test were performed for distribution of scores. T-test or Mann-Whitney test were applied to compare the average ranks between variables with two groups, Kruskal-Wallis test for variables with more than two groups and Dunn test for post-hoc comparisons. To associate variables and QoL scores, the chi-square test, Fisher or Fisher-Freeman-Halton, and z test for post-hoc comparisons were applied. Correlation analysis based on Spearman's rho was applied to compare quantitative variables. The odds ratio (OR) and 95% confidence interval were calculated. A value of P<0.05 was considered significant. The software Statistical Package for the Social Sciences (SPSS) v. 23.0 was used for analysis. Project approved by the Research Ethics Committees of the Federal University of Ceará and other institutions. Following the guidelines of Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). QoL was satisfactory in 74.7% of the seroconcordant and 81.1% of the serodiscordant, with no difference between groups. Females and those who did not accept the diagnosis had lower scores in all domains. Unemployed, with sickness/leave aid, income less than one salary and who suffered stigma/prejudice had lower scores in most domains. Used condoms more consistently, 35.8% of seroconcordant and 50.5% of serodiscordant, with no difference in self-efficacy between groups. There was more inconsistent use in married/stable union (P=0.027), other religions and atheists (P=0.001), who lived with a partner (RC=2.0; P=0.013), with a fixed partnership (P=0.009), with sexual intercourse under the influence of alcohol (OR=3.2; P=0.036), passage through the prison system (OR=1.8; P=0.046), without access to anti-HIV testing (OR=3.2; P=0.005) and dissatisfied with health care. Among the seroconcordant, self-efficacy was lower among Catholics and Evangelicals (P=0.002), with children (P=0.023), with more than three people in the house (P=0.005), without condom use in the last 12 months (P = 0.043), without changing each route (P=0.002) and with difficulty in monitoring health (P=0.046). There was more inconsistent use among those with a fixed partner (P=0.002), whereas those who changed the condom every time (P<0.001) and used it in the last sexual intercourse (P<0.001) had more consistent use. For serodiscordants, self-efficacy was lower among those with children (P=0.042), who did not change the condom each route (P=0.003), without guidance on HIV/other STI prevention (P=0.027) no access to HIV testing (P=0.002). When compared to seroconcordant individuals, they were more likely to use a condom consistently (P=0.028) at the last sexual intercourse (OR=3.0; P<0.001). Condom use was more consistent in those who used it in the last intercourse (P<0.001), in the last 12 months (P<0.001), with change each route (P=0.037) and satisfaction with health care (P= 0.001). It is concluded that QoL and self-efficacy in condom use are similar between seroconcordant and serodiscordant PLHIV, but some variables are associated with unsatisfactory QoL, lower selfefficacy and inconsistent condom use.